Association of Long Term Exposure to Particulate Matter and Ozone with Health Status and Mortality in Patients after Myocardial Infarction. - Malik, Ali O. (Circ Cardiovasc Qual Outcomes, 2019)
BACKGROUND: Long term exposure to particulate matter <2.5μm in diameter (PM(2.5)) and ozone has been associated with the development and progression of cardiovascular disease and, in the case of PM(2.5), higher cardiovascular mortality. Whether exposure to PM(2.5) and ozone is associated with patients’ health status and quality of life, is unknown. We used data from two prospective myocardial infarction (MI) registries to assess the relationship between long-term PM(2.5) and ozone exposure with health status outcomes one year after a MI. METHODS AND RESULTS: TRIUMPH and PREMIER enrolled patients presenting with MI at 31 U.S. hospitals between 2003 and 2008. One year later, patients were assessed with the disease-specific Seattle Angina Questionnaire (SAQ) and 5-year mortality was assessed with the Centers for Disease Control’s National Death Index. Individual patients’ exposures to PM(2.5) and ozone over the year after their MI were estimated from the EPA’s Fused Air Quality Surface Using Downscaling tool that integrates monitoring station data and atmospheric models to predict daily air pollution exposure at the census tract level. We assessed the association of exposure to ozone and PM(2.5) with 1-year health status and mortality over 5-years using regression models adjusting for age, sex, race, socioeconomic status, date of enrollment and comorbidities. In completely adjusted models, higher PM(2.5) and ozone exposure were independently associated with poorer SAQ summary scores at 1-year (β estimate per +1 SD increase = −0.8 (95% CI −1.4, −0.3 p=0.002) for PM(2.5) and −0.9 (95% CI-1.3, −0.4 p<0.001) for ozone). Moreover, higher PM(2.5) exposure, but not ozone, was independently associated with greater mortality risk (HR = 1.13 per +1 SD (95% CI = 1.07-1.20, p<0.001). CONCLUSIONS: In our study, greater exposure to PM(2.5) and ozone was associated with poorer 1-year health status following an MI, and PM(2.5) was associated with increased risk of 5-year death.